ANALYSIS OF TAX COURT APPEAL DECISIONS ON INDIVIDUAL INCOME TAX ARTICLE 25/29 DISPUTES 2019 TO 2022 - Ratnasari, Kenny Rahayu; Nuryanah, Siti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to analyze the development of Individual Income Tax (Pajak Penghasilan Orang Pribadi - PPh OP) disputes in the Tax Court, the characteristics of Individual Taxpayers (Wajib Pajak Orang Pribadi - WPOP) who file Individual Income Tax disputes in the Tax Court, and the factors causing Individual Income Tax Article 25/29 disputes. The research was conducted using the content analysis method. The results show that the development of the Personal Income Tax Article 25/29 decision in the period 2019 to 2022 in the Tax Court is as follows: experiencing an upward trend, based on the tax year appealed tends to experience a fluctuating trend, more in favor of the DGT, and 59.18% of the dispute value is below 4.8 billion rupiah. The characteristics of taxpayers who filed disputes are as follows: 86% are male, 21 taxpayers are identified as private employees, 21 taxpayers reside in DKI Jakarta, and during the trial at the Tax Court, 42 taxpayers used legal counsel. Disputes on Income Tax Article 25/29 (PPh OP) from 2019 to 2022 can be classified into two major classifications, namely formal and material disputes. Formal disputes are caused by the Appellant not knowing the fulfillment of tax obligations properly and correctly, the Appellant making mistakes / mistakes in filling out the tax return, and the Appellant not carrying out tax obligations. Meanwhile, in material disputes, the three biggest causes related to net disputes were caused by the absence of adequate evidence of mutations in the Appellant's account, differences in views and evidence in relation to share transactions, and the status of asset ownership. Keywords: Tax Court, Tax Court Decision, Tax Dispute, PPh OP, Individual Income Tax Article 25/29